Globally asymptotic stability and synchronization analysis of uncertain multi‐agent systems with multiple time‐varying delays and impulses. (26th October 2021) - Arockia Samy, Stephen; Cao, Yang; Ramachandran, Raja; Alzabut, Jehad; Niezabitowski, Michal; Lim, Chee Peng
Abstract: This article interrogates the issue of global asymptotic stability and synchronization analysis of uncertain multi‐agent systems (MASs) with multiple time‐varying delays (discrete and distributed) and impulsive perturbations. In this problem, we prove the existence and uniqueness of the equilibrium point using Brouwer degree properties for the addressed MASs. By applying the approach of Lyapunov–Krasovskii function into the considered system, we achieve the global asymptotic stability and the synchronization criteria by designing the pining control strategy into the MAS. Finally, we provide two numerical calculations along with the computational simulations to check the validity of the theoretical findings reported in this article.